The Impact of Technological Advancements on Criminal Law Amidst Global Digitalization - Elisabeth S Telussa; Alynne H Matulapelwa; John D Pasalbessy (Legtimacy: Journal of Law and Islamic Law, 2026)
This study analyzes the transformative impact of global digitalization, specifically Artificial Intelligence and the Metaverse, on criminal law doctrines. Utilizing a normative-juridical approach, it critically examines the United Nations Convention Against Cybercrime 2024 as a pivotal yet controversial instrument affecting state sovereignty and human rights through expanded passive personality jurisdiction. The research highlights the "jurisdictional creep" phenomenon and the complexities of establishing locus delicti in a borderless cyberspace. Contextualizing these global shifts within Indonesia, the analysis reveals significant vulnerabilities in domestic infrastructure, evidenced by recent ransomware attacks, and a regulatory disconnect between current national statutes and international standards. Consequently, this article advocates for a paradigm shift from rigid territorial positivism toward progressive legal enforcement strategies. It concludes that effective digital sovereignty requires harmonizing cross-border evidence mechanisms and strengthening judicial oversight to balance national security with individual privacy rights within an evolving transnational criminal ecosystem.